Gender Differences in Language Use Among EFL Students : A Sociolinguistic Analysis - Wahyuni; Siti Ainun Kelsaba; Andi Nirwana Humairah A.N; Fitri Arisanti; Saiful; Qalbi (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2026)
This study examines gender differences in language use among EFL students from a sociolinguistic perspective. The research aims to explore how male and female students differ in their interaction patterns, politeness strategies, levels of formality, and the influence of social and cultural norms in English classroom communication. A descriptive quantitative research design was employed, using a questionnaire as the primary instrument to collect data from third-semester students of the English Language and English Education Study Programs. The data were analyzed by categorizing responses based on gender and conducting a comparative analysis to identify patterns of language use and sociolinguistic variation. The findings reveal that both male and female students actively participate in English classroom interactions; however, notable differences emerge in their communication styles. Male students tend to demonstrate higher confidence, more direct speech, and greater dominance in classroom discussions. In contrast, female students generally employ more indirect language, higher levels of politeness, and greater use of mitigating expressions to maintain social harmony. The results also indicate that students adjust their language use according to interlocutors and social context, particularly when interacting with lecturers versus peers. Furthermore, cultural values and social norms play a significant role in shaping students’ language choices and interaction strategies, sometimes exerting a stronger influence than gender alone. Overall, the study concludes that language use among EFL students is not solely determined by linguistic competence but is shaped by a complex interaction of gender, sociocultural norms, and contextual factors. These findings highlight the importance of integrating sociolinguistic awareness into EFL instruction to foster more inclusive and effective classroom communication.